2016
DOI: 10.3389/fvets.2016.00040
|View full text |Cite
|
Sign up to set email alerts
|

Canine Butterfly Glioblastomas: A Neuroradiological Review

Abstract: In humans, high-grade gliomas may infiltrate across the corpus callosum resulting in bihemispheric lesions that may have symmetrical, winged-like appearances. This particular tumor manifestation has been coined a “butterfly” glioma (BG). While canine and human gliomas share many neuroradiological and pathological features, the BG morphology has not been previously reported in dogs. Here, we describe the magnetic resonance imaging (MRI) characteristics of BG in three dogs and review the potential differential d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Reported human and canine butterfly gliomas to date are HAs; however, our findings indicate that, as in gliomatosis cerebri, this represents a pattern of spread rather than a distinct nosologic entity. 19,24,53 Extension of glioma to the pituitary gland had not been described in dogs and has only been confirmed once in humans. 54 Other infrequent features reported here include penetration into the bone and multifocal distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported human and canine butterfly gliomas to date are HAs; however, our findings indicate that, as in gliomatosis cerebri, this represents a pattern of spread rather than a distinct nosologic entity. 19,24,53 Extension of glioma to the pituitary gland had not been described in dogs and has only been confirmed once in humans. 54 Other infrequent features reported here include penetration into the bone and multifocal distribution.…”
Section: Discussionmentioning
confidence: 99%
“…8,17,19,23 Extension through the corpus callosum into the contralateral hemisphere was documented as butterfly glioma. 19,24 Gliomatosis cerebri growth pattern was recorded as recently defined. 19,25 Evidence of extension into the subarachnoid space (tumor spread through the pia mater with or without proliferation within the leptomeninges), ventricular invasion or drop metastases was noted.…”
Section: Morphologic Diagnosismentioning
confidence: 99%
“…The histopathological and diagnostic imaging features of canine gliomas ( Figure 1) are also remarkable similar to their human counterparts (31)(32)(33)(34)(35). These shared morphologic features facilitate comparative classification and grading of tumors using World Health Organization criteria (36) and performing objective imaging-based therapeutic response assessments using the Response Assessment in Neuro-Oncology (RANO) system criteria (28,37).…”
Section: Spontaneous Canine Gliomas As a Faithful Model Of Human Diseasementioning
confidence: 78%
“…Therefore, both DWI and DSC-PWI have been applied in the clinical imaging of human GBM as surrogate markers for tumorigenicity and angiogenesis, reflecting GBM grade and prognosis [19,33]. Previous studies that mentioned spontaneously arising GBM in the canine model reported that the imaging and pathologic features of spontaneous GBM were similar to those characteristics of human GBM [34,35]. However, these studies did not use the current clinical imaging MRI technique using DWI and DSC-PWI but only showed necrotic peripheral enhancing lesions on the conventional MRI technique.…”
Section: Plos Onementioning
confidence: 99%